Biochar supply‐chain and challenges to commercialization. Issue 1 (25th October 2022) - Zilberman, David; Laird, David; Rainey, Coleman; Song, Jie; Kahn, Gabriel
Abstract: Produced through pyrolysis, biochars are used as a soil amendment. Differences in feedstock and processing result in differentiated products which impact their values in different soil conditions. Despite the enormous potential, biochars have not been widely used. This paper overviews the benefits and potential demand for biochar and features of supply chain, and identifies opportunities for viable introduction of biochars. The value of biochars should be evaluated as a part of the pyrolysis system that coproduces biochars and biofuels. Biochars can improve agricultural productivity and soil functioning and contribute to climate change mitigation through carbon sequestration. Furthermore, it can provide extra benefit by contributing to fire prevention. The cost of biochar system depends on the costs of feedstock acquisition, transportation, and processing. Biochar is most likely to be adopted in locations with marginal land and high‐value crop, and near low‐cost feedstock sources. The adoption of biochar can be enhanced by compensation for carbon sequestration, further investment in research, and learning of producers to enhance efficiency of the supply chain. Abstract : Biochar is a charcoal that has been used to improve soil quality. It is obtained through heating organic materials such as crop and forest residues without oxygen. Diverse types of biochar can be coproduced with biofuels. The paper reviews the benefits and potential demand of biochar, and features of the supply chain that would be used to produce and market it. Biochar can improve agricultural productivity and mitigate climate change. Current adoption is low but will be improved with compensation for carbon sequestration, placing processing facilities closer to the biomass sources, and investment in research to reduce cost of production.